2018
DOI: 10.1002/14651858.cd012290.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Active mind-body movement therapies as an adjunct to or in comparison with pulmonary rehabilitation for people with chronic obstructive pulmonary disease

Abstract: Active mind-body movement therapies as an adjunct to or in comparison with pulmonary rehabilitation for people with chronic obstructive pulmonary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“… 10 11 In AE, mind–body exercises such as traditional Chinese exercises (TCEs) can significantly improve the QoL of patients with COPD compared with walking training. 12 Our previous studies also found that TCEs significantly improved lung function, exercise capacity and QoL in patients with COPD. 13 14 Moreover, a study that applied 6-month Baduanjin for patients with COPD found significant improvements in global cognitive function (GCF; measured by Mini-Mental State Examination (MMSE), as well as by P300), psychological functions (measured by the Hamilton Anxiety Scale (HAMA), and the Hamilton Depression Scale (HAMD)), and QoL.…”
Section: Introductionmentioning
confidence: 77%
“… 10 11 In AE, mind–body exercises such as traditional Chinese exercises (TCEs) can significantly improve the QoL of patients with COPD compared with walking training. 12 Our previous studies also found that TCEs significantly improved lung function, exercise capacity and QoL in patients with COPD. 13 14 Moreover, a study that applied 6-month Baduanjin for patients with COPD found significant improvements in global cognitive function (GCF; measured by Mini-Mental State Examination (MMSE), as well as by P300), psychological functions (measured by the Hamilton Anxiety Scale (HAMA), and the Hamilton Depression Scale (HAMD)), and QoL.…”
Section: Introductionmentioning
confidence: 77%
“…Mind–body movement therapies (eg, yoga, tai chi and qigong) may be preferred by some patients, and when compared with conventional training modalities, outcomes related to breathlessness are similar. 51 Low-intensity resistance training using novel approaches, for example, neuromuscular muscle stimulation 52 or partitioned training, may be suited to patients where exertional breathlessness is severely limiting. 53 The low ventilatory demand of these modalities allows the severely breathless patient to exercise to help counteract the deconditioning associated with physical inactivity.…”
Section: Managementmentioning
confidence: 99%
“…Cochrane reviews have examined the role of waterbased exercise, 34 active mind-body movement therapies (e.g. yoga, tai chi) 35,36 and neuromuscular electrical stimulation (NMES) 37 in COPD.…”
Section: Exercise In Water Active Mind-body Movement Therapies and Neuromuscular Electrical Stimulationmentioning
confidence: 99%
“…38 However, adding Tai Chi to a traditional exercise program does not appear to provide any additional benefit. 35 Adding NMES of the peripheral muscles has also been trialled as a strategy to improve exercise capacity. This intervention involves placing conductive pads over the muscle (usually the quadriceps) that are then attached to a stimulation unit.…”
Section: Exercise In Water Active Mind-body Movement Therapies and Neuromuscular Electrical Stimulationmentioning
confidence: 99%